LEGAL RESPONSIBILITIES OF THE INDEPENDENT INSTITUTION AS THE ASSESSOR OF ACCREDITATION OF GOVERNMENT HOSPITALS - Nabella, Tamima Izzat; Asmuni, Asmuni; Pramono, Budi (JILPR Journal Indonesia Law and Policy Review, 2024)
There are still cases of hospital accreditation manipulation, highlighting the importance of the existence of independent institutions as assessors of government hospital accreditation. Therefore, two research questions arise: the regulation of independent institutions as assessors of government hospital accreditation and the administrative legal accountability of independent institutions as assessors of government hospital accreditation. This study is a normative legal research employing several approaches, including legislative approach, conceptual approach, and comparative approach. The results show that the authorization given to independent institutions in accrediting hospitals is regulated by Law Number 17 of 2023 concerning Health, aiming to create consistency, harmony, systematicity, and synchronicity in efforts to improve the quality of health services. These provisions are reinforced by regulations such as the Hospital Law, Minister of Health Regulation Number 12 of 2020, and Minister of Health Decree Number HK.01.07/MENKES/406/2020 jo. Minister of Health Decree Number HK.01.07/MENKES/6604/2021, and Minister of Health Decree Number HK.01.07/MENKES/1128/2022, demonstrating the accountability, consistency, and systematic nature of the legal basis needed. The administrative legal accountability of independent institutions as assessors of government hospital accreditation has administrative legal consequences, namely the revocation of the Minister of Health's decree that approves their status as hospital accreditation providers.